Manajemen Guru Mengajar Bahasa Inggris - Herman Herman; M. Dimas Bagus Nurmuzayyin; Sholahuddin Irsyad; Khuzanah Khuzanah; Ida Rindaningsih (FKIP, Universitas Palangka Raya, 2024)
Management is an inseparable part of a teacher in teaching, because organizing the course of learning is very important, so that the knowledge transferred by the teacher can be digested and understood by students. This study aims to determine teacher management in teaching. This type of research is descriptive qualitative to obtain information about the teacher's management of teaching English at grade 1 elementary school. The results of this study indicate that the teacher's management of teaching is not only transferring the knowledge possessed. Teachers have an important role to understand the character of learners who come from different backgrounds. Teachers can evaluate learning directly or indirectly, learning reflections, daily assessments, midterm and end-of-semester assessments to find out the results of students while learning in class.